Cement leakage in percutaneous vertebroplasty for spinal metastases: a retrospective study of risk factors and clinical outcomes - Wang, Lin; Zhang, Chao; Liang, Hao; Huang, Tianji; Zhong, Weiyang; Zhao, Zenghui; Luo, Xiaoji (World journal of surgical oncology, 2022)
Objective The objective of this research was to investigate the risk factors of cement leakage in patients with metastatic spine tumors following percutaneous vertebroplasty (PVP). Methods Sixty-four patients with 113 vertebrae were retrospectively reviewed. Various clinical indexes, including age, sex, body mass index (BMI), smoking history, drinking history, chemotherapy history, radiotherapy history, primary cancer, location, other metastases, collapse, posterior wall defects, the laterality of injection, and the injected cement volume were analyzed as potential risk factors. Multivariate analyses were conducted to identify the independent risk factors. Results The cement leakage was found 64 in 113 treated vertebrae (56.63%), in which the incidence of each type was shown as below: spinal canal leakage 18 (15.93%), intravascular leakage around the vertebrae 11 (9.73%), and intradiscal and paravertebral leakage 35 (30.97%). Tomita classification ( P = 0.019) and posterior wall destruction ( P = 0.001) were considered strong risk factors for predicting cement leakage in general. The multivariate logistic analysis showed that defects of the posterior wall ( P = 0.001) and injected volume ( P = 0.038) were independently related to the presence of spinal canal leakage. The postoperative visual analog scale (VAS) and activities of daily living (ADL) scores showed significant differences compared with the pre-operative parameters ( P < 0.05). No significant differences were found in every follow-up time between the leakage group and the non-leakage group for pain management and improvement of activities in daily life. Conclusion In our study, Tomita classification and the destruction of the posterior wall were independent risk factors for leakage in general. The defects of the posterior wall and injected volume were independently related to the presence of spinal canal leakage. The PVP procedure can be an effective way to manage the pain.